1999
DOI: 10.1055/s-2008-1072249
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation in Short-Bowel Syndrome in Rats

Abstract: Massive intestinal resection results in short-bowel syndrome (SBS) and is associated with an increased risk of infectious complications mainly caused by the egress of intestinal bacteria to distant organs, a process termed bacterial translocation (BT). The purpose of this experimental study in rats was to investigate in different models of SBS the impact of the type of intestinal resection on bacterial growth in the residual small bowel and on the occurrence of BT. SBS was created in 30 rats either by jejunal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The ''Principles of laboratory animal care'' (NIH publication No. 86-23, revised 1985) were followed and all experiments were conducted with the permission of the animal research commission of the Austrian Ministry of Science following local guidelines for the use and care of laboratory animals [5,18]. The rats were housed in an environmentally controlled vivarium with a 12 h lightdark cycle and received a standard pellet diet and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…The ''Principles of laboratory animal care'' (NIH publication No. 86-23, revised 1985) were followed and all experiments were conducted with the permission of the animal research commission of the Austrian Ministry of Science following local guidelines for the use and care of laboratory animals [5,18]. The rats were housed in an environmentally controlled vivarium with a 12 h lightdark cycle and received a standard pellet diet and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies using animal models have demonstrated that this kind of surgery leads to an increase in permeability of the remaining bowel (29) and bacterial translocation (30). These phenomena could be related to the absorption of endotoxins and bacterial lipopolysaccharides, increasing TNF-α levels and finally leading to steatohepatitis (31).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of liver injury, cholestasis, and septic episodes may be reduced when measures are taken to reduce or modify bacterial levels in the gut lumen (25,36,59). In animal models of intestinal resection, an increased incidence of bacteria cultured from mesenteric lymph nodes has been demonstrated (40,44).…”
mentioning
confidence: 99%